A rare case of congenital ranula - Nitinkumar Bhajandas Borkar (African Journal of Paediatric Surgery, 2021)
Simple ranula is a cystic swelling confined to the floor of mouth while plunging ranula presents with extension to the neck. Congenital ranula presenting with symptoms of feeding difficulties is a very rare occurrence. There is paucity of literature regarding the management of large congenital ranula. Varied treatment options are described for the management of ranula with variable recurrence rate. In paediatric and adult patients, ranula is considered as a type of extravasation cyst and removal of sublingual gland is advocated to remove the sources of extravasation. Congenital ranula is usually a variant of retention cyst and should be treated with marsupialisation or simple excision of cyst while cyst excision with sublingual sialadenectomy should be reserved for recurrent cases.